Analisis Pengaruh Marketing Mix terhadap Keputusan Taruna/I Memilih Kampus Politeknik Pelayaran - Dapid Rikardo; Adnan Adnan; Joni Turiska (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aimed to analyze the influence of the marketing mix on the decision of the cadets to choose the Banten Shipping Polytechnic campus. This research method is a quantitative research method with a survey method conducted at Poltekpel Banten, starting from January 2020 to May 2020. The research process is deductive in nature with the research population being Banten Poltekpel alumni. From the population, 199 cadets were taken as samples. This study uses a questionnaire to measure the simulation learning media. The results showed that all CR values ​​> 1.96 and P < 0.05, namely, a) product satisfaction with cadets with a CR value of 2.765 > 1.96; b) the price for the decision of the cadets with the value of CR = 2,400 < 1.96; c) promotion of cadet decisions with a CR value of 2.563 > 1.96; d) the place or location of the cadets' decisions with a CR value of 2.801 > 1; e) people against cadet decisions with CR = 2,217 > 1; f) process for cadet decisions with CR value = 2.801 < 1.96; g) physical evidence of cadet decisions with CR = 2.480 > 1.96. The conclusion is that the product, price, promotion, location, people, process, and physical evidence have a positive and significant impact on the cadets' decision in choosing the Banten Shipping Polytechnic campus as a place to override education. Keywords: Youth Decision, Marketing Mix, Institutional Management